2018
DOI: 10.2478/ngoe-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Behavioral Symptoms of Burnout on Work Engagement of Older Employees: The Case of Slovenian Companies

Abstract: The main objective of the paper is to determine the impact of behavioral symptoms of burnout of older employees on their work engagement in large- and mediumsized companies in Slovenia. The research is based on the implementation of a factor analysis by which we wanted to reduce the large number of variables into a smaller number of factors. With those factors, we performed a simple linear regression. Based on the results, we confirmed the hypothesis that behavioral symptoms of burnout of older employees have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…BO refers to a persistent, negative work-related state of mind (or syndrome), which is characterised by an array of physical, psychological, and attitudinal symptoms [8,33]. It is a chronic, negative, affective response, with fatigue and emotional exhaustion as major symptoms [34].…”
Section: Burnout (Bo)mentioning
confidence: 99%
See 3 more Smart Citations
“…BO refers to a persistent, negative work-related state of mind (or syndrome), which is characterised by an array of physical, psychological, and attitudinal symptoms [8,33]. It is a chronic, negative, affective response, with fatigue and emotional exhaustion as major symptoms [34].…”
Section: Burnout (Bo)mentioning
confidence: 99%
“…WE and BO are conceptualised to be opposing constructs on the ease-disease continuum, while vigour and dedication are the direct opposites of exhaustion and mental distance (cynicism) [3]. Previous research has found that WE and BO relate closely to work-associated well-being [8,52], while managing job burnout prevents ill-health outcomes [1,41,53].…”
Section: Sense Of Coherence Burnout and Work Engagement Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike physical hazards, which are directly observable and measurable, psychosocial risks are the product of social interactions, and cannot be understood outside their context [7]. Some of the psychosocial factors associated with work burnout are: new hiring schemes and job insecurity, aging of the workforce, task intensification, high emotional demands at work, poor work-life balance, long shifts, higher workloads, poor salary and promotion prospects, ambiguous roles, and time and cost pressures that increase the risk of errors or compromise ethical and quality standards [8,9].…”
Section: Psychosocial Risk Factorsmentioning
confidence: 99%